Solar Drying as an Eco-Friendly Technology for Sewage Sludge Stabilization: Assessment of Micropollutant Behavior, Pathogen Removal, and Agronomic Value - An-nori, Amal; Ezzariai, Amine; El Mejahed, Khalil; El Fels, Loubna; El Gharous, Mohamed; Hafidi, Mohamed (Frontiers in Environmental Science, 2022)
Sewage Sludge (SS), a byproduct of wastewater treatment, is a complex biosolid that includes nutrients, organic matter but also a mixture of micropollutants and microorganisms. When intended to be recycled in agriculture, several criteria should be met to avoid the dissemination of the included hazardous material and then to limit their negative implications on the environment. Hence, adequate treatment should be applied prior to its disposal. Among the stabilizing treatments, solar drying, which is an extended dewatering technique, is commonly used to remove water from SS. This process, based mainly on solar radiation, has further impacts on SS physicochemical and biological quality. This review highlights the state of the art with regard to solar drying impact on water content in SS and the occurring micropollutants including pathogens, Heavy metals (HMs) and Polycyclic Aromatic Hydrocarbons (PAHs) and antibiotics. Two drying cycles are commonly investigated in literature: summer and winter addressing thus the extreme conditions met within a year with respect to temperature, insolation and hygrometry. The efficiency of solar drying in terms of dry matter increase is widely reported in literature. Under different climatic conditions, more than 80% of dry matter is reached during summer season. However, in winter, the efficiency decreases to 50% of DM. Negatively correlated to DM content, pathogens concentration in sludge significantly decreases while DM increases. Thus, more efficiency in terms of pathogens abatement is reported in summer compared to winter. Several authors reported the reliance of solar drying efficiency on whether in terms of pathogens removal as the main shortcoming of the studied process. Consequently, where climatic conditions are not favorable for solar drying, hybrid design, which includes another source of heat, and liming are the highly recommended alternatives. The few studies on the fate of HMs in SS during solar drying concluded that solar drying does not involve any removal mechanisms. However, changes in HMs speciation were reported, highlighting a decrease in their availability. As for organic micropollutants (PAHs and antibiotics), only their occurrence in SS is reported in literature and their behavior during solar drying process is still not addressed.